Bad Timing: The Temporal Dimensions of Economic Insecurity. (July 2020) - Banks, Marcus; Bowman, Dina
In this article, we draw on a recent Australian study to illustrate how social time in precariously employed or low-income households is increasingly riven by uncertainty and risk. We apply two concepts, riskscapes and timescapes, to examine how these households respond to and are buffeted by the economic and temporal insecurities they experience in labour, welfare and finance markets. Using May and Thrift's four categories of time, – representations, technologies, social disciplines and rhythms – we highlight how household timescapes interact with their riskscapes to exacerbate economic insecurity.